2018
DOI: 10.1177/0047117818802436
|View full text |Cite
|
Sign up to set email alerts
|

A structural-relational analysis of party dynamics in proxy wars

Abstract: Proxy wars are still under-represented in conflict research and a key cause for this is the lack of conceptual and terminological care. This article seeks to demonstrate that minimizing terminological diffusion increases overall analytical stability by maximising conceptual rigor. The argument opens with a discussion on the terminological ambivalence resulting from the haphazard employment of labels referencing the parties involved in proxy wars. Here, the article introduces an analytical framework with a twof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…5 We expect a sponsor’s fear of rebels’ non-compliance to be significantly diminished by shared ethnic ties. While aligned goals between a rebel group and a sponsor might stem from a diversity of sources (Rauta 2018; San-Akca 2016), ethnic ties between a sponsor and a rebel group indicate shared or at least compatible goals in many conflict settings (see Saideman 1997, 2001, 2002; Maoz and San-Akca 2012; Cederman, Girardin, and Gleditsch 2009; Cederman et al 2013; Salehyan 2010, 505; Byman and Kreps 2010, 5). Ethnic ties might also provide both parties with information about each other.…”
Section: Explaining State Sponsors’ Choice Between Orchestration and Delegationmentioning
confidence: 99%
“…5 We expect a sponsor’s fear of rebels’ non-compliance to be significantly diminished by shared ethnic ties. While aligned goals between a rebel group and a sponsor might stem from a diversity of sources (Rauta 2018; San-Akca 2016), ethnic ties between a sponsor and a rebel group indicate shared or at least compatible goals in many conflict settings (see Saideman 1997, 2001, 2002; Maoz and San-Akca 2012; Cederman, Girardin, and Gleditsch 2009; Cederman et al 2013; Salehyan 2010, 505; Byman and Kreps 2010, 5). Ethnic ties might also provide both parties with information about each other.…”
Section: Explaining State Sponsors’ Choice Between Orchestration and Delegationmentioning
confidence: 99%
“…Overlapping war and warfare as well as the dynamics of terrorist and insurgent violence, the adjective "proxy" came to delineate a category of thought complicated "by the myriad of forms that proxy intervention can take" (Loveman, 2002, p. 31). As discussion of definitions already exist in in the literature (Rauta, 2018), two observations are relevant here because they link to the search for knowledge gaps and the types of questions the framers asked. First, what might be regarded as conceptual disarray 3 is the by-product of the framers rediscovering a concept with slightly compromised analytical capital-due to the pioneering, yet hugely diverse Cold War literatures of the founders.…”
Section: Framersmentioning
confidence: 99%
“…Yet, even when accounting for trends and fashions, a closer inspection reveals multiple barriers of entry into the debate, across fields and disciplines, each with conceptual, theoretical, and methodological preferences. As previously remarked, these include Cold War historiography, covert action and secrecy, and conflict and terrorism research (Rauta, 2018). Moreover, proxy war literature pushed through by ignoring some of this research, and by being ignored by others in return, 1 in such a way that it emerged and evolved in and from relative anarchy with multidisciplinarity disguised as interdisciplinarity (Barkawi, 2011, p. 707).…”
mentioning
confidence: 99%
“…As Carey and Mitchell recently put it, governments often 'settle for less than a monopoly of violence ' (2017, 128), with proxies being one conduit of managing this situation. Recent scholarly efforts have refined our understanding of proxies (Berman and Lake 2019; Rauta 2018;Waldman 2018;Mumford 2013;Hughes 2012), delineated between proxy and auxiliary relationships (Rauta in Brown et al 2019Scheipers 2015), and identified surrogacy as a standalone strategic relationship Waldman 2019;Krieg 2016;Hughes and Tripodi 2009). The complexity of the consumption and management of violence in contemporary settings, and the differences between proxies, auxiliaries, and surrogates are relevant to the hybrid warfare debate.…”
Section: The Actor Problem In Hybrid Warfare Researchmentioning
confidence: 99%